Public school: spacetime for weaving knowledge in dialogue with children from popular classes (Práxis Educativa, 2024)
The article proposes a reflection on the place of the popular class children and their childhoods within the pedagogical processes carried out in Basic Education in public institutions. It is based on qualitative research conducted by teachers in their contexts of practice, using everyday life research as a method and drawing on records of school experiences and the works of both teachers and students through various forms of expression. The work of the teacher-researchers is articulated within the Doctoral program, referenced in the liberating education in the Freirean sense, as well as decolonial and anti-racist studies. With children, assumed as social and political subjects, teaching finds the power of dialogue, a hallmark of popular education, mobilizing experiences in public education as a spacetime conducive to the weaving of creative and transformative knowledge.Keyword: Childhoods. Dialogue. Popular classes.